Legal Ratio of Income Tax Regulation Towards Transfer of Rights on Land and Building - Stephanie Wilamarta; Sudarsono Sudarsono; Abdul Rachmad Budiono; Bambang Sugiri (Wacana Journal of Social and Humanity Studies, 2018)
Regulations concerning income tax on rights and land in the form of buying and selling, grants and inheritance, are regulated in law number 36 of 2008, Government Regulation number 34 of 2016 and Circular of Director General of Tax number SE-20 / PJ / 2015. Some of the regulations that are considered not fulfilling the element of justice, so there is a need for research to find out about the income tax. land and buildings in the form of buying and selling, grants and inheritance focusing on the principles of justice and certainty law. The method used in This research is normative legal research using four methods of approach, namely legislation approach, conceptual approach, historical approach, and comparative approach. The results showed that justice in tax was regulated by the Government Regulation Number 79 of 1994 in conjunction with Government Regulation Number 79 of 1999 specifically regulates the imposition of Income Tax income from the transfer of rights to land and buildings with the final tariff, so that for transactions that are losing (without additional economic capability) will still be subject to income tax. The income tax collection is on income from the right, because it does not fulfill the convenience of convenience taxation, namely the imposition of tax on the transfer of rights to land transactions, especially Income Taxes. tax collection based on profit or gross income less costs (Pay as you earn).